2022
DOI: 10.31083/j.jin2101013
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological correlates of cerebellar volumes in multiple sclerosis: an MRI volumetric analysis study

Abstract: The hallmark of Multiple Sclerosis (MS) pathophysiology is the damage to the myelin sheath around axons. The cerebellum is a predilection site for demyelination with a well-recognized role in motor and a rather understudied contribution to cognitive functions. The aim of this study is to investigate patterns of cerebellar grey and white matter pathology, expressed as reduced volume, as well as cortical thickness and their potential contribution to cognitive performance and disability status of patients with MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Inflammation in optic neuritis causes neurodegeneration in visual pathways as well as anterograde (retina to cortex) and retrograde (cortex to the retina) transsynaptic functional changes (Davion et al, 2020). Atrophy of brain regions has been demonstrated in many neurodegenerative processes, including disease or senility (Author & Javadi, 2019; Coupé et al, 2017; Iliadou et al, 2022). Our study's strength was that patients with neurological, autoimmune disease, and trauma history and MRI findings of senile cerebral atrophy or demyelinated plaques were omitted.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation in optic neuritis causes neurodegeneration in visual pathways as well as anterograde (retina to cortex) and retrograde (cortex to the retina) transsynaptic functional changes (Davion et al, 2020). Atrophy of brain regions has been demonstrated in many neurodegenerative processes, including disease or senility (Author & Javadi, 2019; Coupé et al, 2017; Iliadou et al, 2022). Our study's strength was that patients with neurological, autoimmune disease, and trauma history and MRI findings of senile cerebral atrophy or demyelinated plaques were omitted.…”
Section: Discussionmentioning
confidence: 99%
“…The authors report considerable cerebellar reorganization decades after the poliomyelitis infection, which may be interpreted as compensation for anterior horn insult in infancy. Moreover, to unveil the contribution of cerebellum to the cognitive deficits of patients with multiple sclerosis (MS), Iliadou et al [14] investigated the patterns of cerebellar GM and WM alterations and their association with cognitive performance and disability status. An interesting finding of their study was the inverse correlation observed between cerebellar volumes and cortical thickness, and scores in the cognitive tests.…”
Section: Introductionmentioning
confidence: 99%